Anti-Tumor Effects of Bak-Proteoliposomes against Glioblastoma - Lavinia Liguori; Fabio Pastorino; Xavier Rousset; Silvia Alfano; Sandra Cortes; Laura Emionite; Antonio Daga; Mirco Ponzoni; Jean-Luc Lenormand (Molecules, 2015)
Despite palliative treatments, glioblastoma (GBM) remains a devastating malignancy with a mean survival of about 15 months after diagnosis. Programmed cell-death is de-regulated in almost all GBM and the re-activation of the mitochondrial apoptotic pathway through exogenous bioactive proteins may represent a powerful therapeutic tool to treat multidrug resistant GBM. We have reported that human Bak protein integrated in Liposomes (LB) was able, in vitro, to activate the mitochondrial apoptotic pathway in colon cancer cells. To evaluate the anti-tumor effects of LB on GBM, MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays and Western blot analysis were performed on GL26 murine cell line. LB treatment shows a dose-dependent inhibition of cell viability, followed by an up-regulation of Bax and a down-modulation of JNK1 proteins. In GL26-bearing mice, two different routes of administration were tested: intra-tumor and intravenous. Biodistribution, tumor growth and animal survival rates were followed. LB show long-lasting tumor accumulation. Moreover, the intra-tumor administration of LB induces tumor growth delay and total tumor regression in about 40% of treated mice, while the intravenous injection leads to a significant increased life span of mice paralleled by an increased tumor cells apoptosis. Our findings are functional to the design of LB with potentiated therapeutic efficacy for GBM.